A breeding colony of Wedge-rumped Storm-Petrel, Oceanodroma tethys kelsalli (Lowe 1925), on Santa Island-Peru - Ayala, Liliana (2008)
The important breeding areas of Wedge-rumped storm petrel were unkwnown until recently. This species breeding in the central cost of Peru: Ferrol, Chao and Corcovado islands. We reported Santa island as a breeding area of this seabird. We located a total of 407 active nests, including 92 (22%) with eggs and 7 (8%) with chicks. Most breeding birds were found in an area near to the guard house in the east of the island,in the south and southwest of the island, where guano birds and large numbers of ticks were registered, we found few storm petrel nests. The south and southwest of the island has a high humidity and several of the dry-stone walls were covered with moss and algae. In those walls no storm petrel nests were found. It is possible other breeding sites exist on the Peruvian coast. Surveys of nesting areas in coastal Peru will provide much-needed information on Wedge-rumped storm-petrel status.